Why Do People Prefer Individual Therapy Over Group Therapy?. Issue 4 (1st October 2016) - Shechtman, Zipora; Kiezel, Abeer
ABSTRACT: The current study aims to identify the reason people avoid group therapy despite its recognized effectiveness. Participants were 224 university students, men and women from two ethnic groups (Jewish and Arab) in Israel. We asked them to mark their preference for individual or group therapy on a 7-point scale and add five arguments in favor and against each type of therapy. Results verified the tendency to prefer individual over group therapy, with minor gender or ethnic effects. Participant arguments indicated accuracy in identifying the strength of group therapy, but various fears limit their enthusiasm about group therapy. The discussion focuses on possible ways to overcome those fears.